Financial Reporting and Corporate Governance in Developing Countries: A literature Review - Barghouthi, Orobah Ali (International Journal of Shari’ah and Corporate Governance Research, 2018)
Transparency is one of those terms that have many facets. It is used in different ways. It can refer to the openness of governmental functions. It can also refer to a country’s economy. Or it can refer to various aspects of corporate governance and financial reporting. The Organisation for Economic Co-operation and Development (OECD, 1998) lists transparency as one element of good corporate governance. Kulzick (2004) and others (Blanchet, 2002; Prickett, 2002) view transparency from a user perspective. According to their view, transparency includes the following eight concepts: accuracy, consistency, appropriateness, completeness, clarity, time- liness, convenience, and governance and enforcement. This paper focuses on just one aspect of transparency – timeliness.